Kecakapan Hidup Untuk Generasi Z: Tantangan Pendidikan Di Abad 21 - Hidayah, Dede Urfah; Novaryansyah, Givan; Arikah, Khopipah; Karwati, Lilis (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Life skills education is crucial for Generation Z growing up in a fast-paced digital era. This journal discusses the unique characteristics of Generation Z, including their dependence on technology, multitasking abilities, and global awareness. However, this generation also faces serious challenges such as moral degradation and loss of identity due to foreign cultural influences. By implementing life skills education that encompasses digital, financial, and cultural literacy, it is hoped that Generation Z can overcome these challenges. Innovative learning methods utilizing technology are essential to enhance their skills and knowledge. Involvement from the government, families, and communities is vital in shaping a positive character that prepares Generation Z for a complex future.